Improving Equity in Tertiary Education in Ghana - Osei-Tutu, Ellen (Journal of Interdisciplinary Studies in Education, 2021)
The sustainable development goals in education by the United Nations aim at inclusive and quality education for all.  To achieve this in Ghana, the Draft Inclusive Education Policy provides an opportunity to address the diverse learning needs of all citizens.  Also, the 1992 constitution   provides the legal basis for the provision of higher education to be equally accessible to all.  Equity in education means making sure that equitable and quality education is accessible to all students. This paper, based on the review of literature identified the gaps that exist and the pathways to closing these gaps to facilitate equity in tertiary education in Ghana. The equity gaps identified include disability, poverty and insufficient use of Information and Communication Technology (ICT).